Hyperuricemic Renal Failure in Nonhematologic Solid Tumors: A Case Report and Review of the Literature - Saini, Neeraj (Hindawi Publishing Corporation, 2012)
Tumor lysis syndrome (TLS) is an oncologic emergency that is caused by massive tumor cell lysis. It is commonly associated with hematological cancers like leukemia and lymphoma and uncommonly with solid nonhematologic tumors as well. However, spontaneous tumor lysis syndrome (STLS) without any cytotoxic chemotherapy rarely occurs in solid tumors. We describe a case of STLS in a metastatic adenocarcinoma of unknown primary and review the literature of STLS in solid non-hematologic tumors to identify various risk factors for pathogenesis of this entity.